سیرت رسول اللہﷺ کی اشتراکی تعبیرات: شرقاوی کی سیرت نگاری کا خصوصی مطالعہ - Ghulam Fatima (Seerat Studies, 2023)
The Egyptian Revolution 1952 brought significant change in the intellectual and socio-political spheres of life of the country. The socialist’s ideas gained popularity among the liberalists, but the religious class remained cautious in accepting the socialist ideas and reforms. To create space for social reforms among the religious minded masses, the Socialist authors attempted to present the religion of Islam as a movement of social change and the Prophet Muhammad as a revolutionary leader who endeavored for social reforms. Abd al-Rahman Al-Sharqawi (d. 1987) was a well-known Egyptian socialist writer. He tried to portray the Prophet Muhammad (peace be upon him) as an exemplary human being who revolutionized the Arab society. This paper aims to analyze al-Sharqawi’s Sirah-writing Muhammad Rasul al-Huriyya (Muhammad- the Messenger of Freedom). Al-Sharqawi opined that there was a plethora of Sirah literature available regarding the life of the Prophet, his beliefs, miracles, and dogmas, whereas little attention had been paid to his human and social perspectives in Sirah-writing. Al-Sharqawi attempted to illustrate the social and humanistic values of the Prophet Muhammad -peace be upon him- and how he brought freedom and harmony to human beings irrespective of their religious or racial affiliations. The present research appraises the extent to which the author successfully composed his Sirah through the application of Socialist terminologies.